2009
DOI: 10.1016/j.jcrs.2008.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and defining the sharpness of intraocular lenses: Microedge structure of commercially available square-edged hydrophilic intraocular lenses

Abstract: Analysis of the microstructure of the optic edge of currently available square-edged hydrophilic acrylic IOLs showed a large variation of the deviation area from a perfect square.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 23 publications
2
28
0
1
Order By: Relevance
“…25 Analysis of the microstructure of the optic edge of currently available square-edged hydrophilic and hydrophobic acrylic IOLs showed a large variation in the deviation from a perfect square, not only between IOL designs but also between different powers of the same IOL design. 26,27 Although both IOLs we implanted in the present study have sharp optic edges, scanning electron microscopic images show that the edge of the hydrophobic IOL is sharper than that of the hydrophilic IOL at the 3 powers evaluated (ie, 15.0 D, 20.0 D, and 25.0 D) (Figure 8).…”
Section: Discussionmentioning
confidence: 61%
“…25 Analysis of the microstructure of the optic edge of currently available square-edged hydrophilic and hydrophobic acrylic IOLs showed a large variation in the deviation from a perfect square, not only between IOL designs but also between different powers of the same IOL design. 26,27 Although both IOLs we implanted in the present study have sharp optic edges, scanning electron microscopic images show that the edge of the hydrophobic IOL is sharper than that of the hydrophilic IOL at the 3 powers evaluated (ie, 15.0 D, 20.0 D, and 25.0 D) (Figure 8).…”
Section: Discussionmentioning
confidence: 61%
“…However, studies suggest that square-edged IOLs should completely encompass the 360 degrees around the IOL optic in order to provide an effective barrier (25) . Furthermore, another study has shown differences between brands of square-edged len- ses, and suggested that variations in their edge profiles may account for clinical differences in postoperative PCO rates (26) . In addition, it has been reported that acrylic IOLs appear to lose their PCO preventive effect, despite their sharp optic edges (27) .…”
Section: Discussionmentioning
confidence: 99%
“…As a group, the edges of silicone IOLs were found to be sharper than those of hydrophobic acrylic and hydrophilic acrylic IOLs. [21][22][23] We hypothesized in the beginning of this study that rates of PCO would be lower in cadaver eyes with square-edged IOLs, assuming both groups of silicone IOLs would induce similar amounts of fibrosis and considering the overall superior sharpness of the edge of square-edged silicone IOLs on the market. Indeed, we found a statistically significant difference in central and peripheral PCO between Nixon 24 showed the advantage of the square edge in silicone IOLs in vivo.…”
Section: Discussionmentioning
confidence: 99%